Hubungan Motivasi dengan Keterampilan Bermain Sepakbola Atlet Sekolah Sepakbola (SSB) Silampari Kota Lubuklinggau Tahun 2021 - Nauval Syarif Hidayatullah; Sukasno; Wawan Syafutra (Silampari Jurnal Olahraga, 2021)
The problem in this study is the unknown motivation of athletes of Silampari Lubuklinggau School of Football (SSB) to know the relationship between motivation and football skills of Athletes of Silampari School of Football (SSB) Lubuklinggau City. The purpose of this study is to find out whether there is a relationship between motivation and the skills of playing athlete football (SSB) Silampari. The research method used in this study is descriptive quantitative research method. The population in this study is all athletes (SSB) Silampari City Football School lubuklinggau which amounts to 30 students. Data collection techniques using questionnaires containing statements about the motivation of athletes in training and documentation in the form of student raport athletes (SSB) Silampari Football School Lubuklinggau City. The data test used is a normality test and then correlated using product moment correlation test. The conclusion obtained from this study is that there is a positive correlation between motivation and football skills of SSB Silampari Athletes in Lubuklinggau City with the results 0,4120.